Relationships of feedlot performance, feeding behavior, rumen morphometrics, and carcass characteristics of Nellore cattle differing in phenotypic residual feed intake - Pereira, M. C. S. [UNESP]; Cruz, G. D.; Arrigoni, M. D. B. [UNESP]; Rigueiro, A. L. N. [UNESP]; Silva, J. [UNESP]; Carrara, T. V. B. [UNESP]; Santos, P. C. S. [UNESP]; Cursino, L. L. [UNESP]; Millen, D. D. [UNESP] (Amer Soc Animal Science, 2016)
The objective of this study was to examine the relationship of DMI fluctuation, feedlot performance, feeding behavior, rumen morphometrics, and carcass characteristics in Nellore cattle classified by residual feed intake (RFI). One experiment was conducted in 2 consecutive years using individual pens (1.0 x 7.0 m) at the Sao Paulo State University feedlot, Dracena campus, Brazil. The experiment in year 1 started in June of 2012 with forty-eight 20-mo-old Nellore yearling bulls with an initial BW of 358.2 +/- 19.4 kg. The experiment in year 2 started in January of 2013 with sixty 20-mo-old Nellore yearling bulls with an initial BW of 402.5 +/- 33.0 kg. Experiments in years 1 and 2 lasted 94 and 84 d, respectively. All yearling bulls were categorized as high RFI (>0.5 SD above the mean, n = 25), medium RFI (+/- 0.5 SD from the mean, n = 56), and low RFI (<0.5 SD below the mean, n = 27). Visual appraisal to collect behavior data was made on d 40 (finishing period) of both years. Yearling bulls were harvested when average across treatment groups achieved a fat thickness of 4 mm at the 12th rib. Low-RFI yearling bulls had lower daily DMI, expressed either in kilograms (P < 0.01) or as percentage of BW (P < 0.01), and improved G:F (P < 0.01) when compared to high-RFI animals. No differences were observed (P > 0.10) for ADG, final BW, or HCW among RFI groups. Also, low-RFI yearling bulls had thinner final 12th rib (P < 0.01) and biceps femoris (P8) fat thickness (P < 0.01). Low-RFI yearling bulls were slower to consume (P = 0.03) and ruminate (P < 0.01) 1 kg of either DM or NDF. No significant (P > 0.10) RFI effect was observed for any ruminal morphometrics variables evaluated, with the exception of papillae area, in which low-RFI Nellore yearling bulls tended to have smaller (P = 0.07) papillae area than medium-RFI animals. In general, low-RFI Nellore yearling bulls consumed more particles larger than 19 and 8 mm and had a similar performance when compared to both medium-and high-RFI bulls; however, carcass fat composition was negatively impacted.
Keywords: carcass; fat; feedlot; Nellore; performance; residual feed intake